Unusual Synchronous Methimazole-Induced Agranulocytosis and Severe Hepatotoxicity in Patient with Hyperthyroidism: A Case Report and Review of the Literature - Jun Yang; Jun Zhang; Qin Xu; Guo-ping Sheng; Wan-wen Weng; Meng-jie Dong (International Journal of Endocrinology)
Context. To report a patient with hyperthyroidism who developed concurrent occurrence of agranulocytosis and severe hepatotoxicity after taking methimazole (MMI). Case. A 51-year-old Chinese male was diagnosed as hyperthyroidism with normal white blood count and liver function. After 4 weeks’ treatment with MMI 20 mg/d, it developed to agranulocytosis and severe cholestatic hepatotoxicity. The patient’s symptoms and laboratory abnormalities disappeared after the withdrawal of MMI; his white blood count and liver function recover to normal in 2 weeks and 5 weeks, respectively. 296 MBq dose of 131I was given to the patient 3 weeks after the withdrawal of MMI and his thyroid function was back to normal in 6 months. As we know through literature review, only 5 previous cases reported the synchronous ATD-induced agranulocytosis and severe hepatotoxicity in patients with hyperthyroidism. Methods. Review of the patient’s clinical course. Literature review of cases of hyperthyroidism with agranulocytosis and severe hepatotoxicity demonstrated that these complications occurred after taking antithyroid drug (ATD). Conclusions. Patient with hyperthyroidism can have synchronous ATD-induced agranulocytosis and severe hepatotoxicity. This case is extremely rare, but the adverse effects with ATDs is clinically significant. The clinicians need to be careful about this and monitor biochemical of patients who take ATDs.